An in vitro assay approach to investigate the potential impact of different doping agents on the steroid profile. Issue 5 (14th December 2020) - Piper, Thomas; Heimbach, Sonja; Adamczewski, Martin; Thevis, Mario
Abstract: The steroid profile, that is, the urinary concentrations and concentration ratios of selected steroids, is used in sports drug testing to detect the misuse of endogenous steroids such as testosterone. Since several years, not only population‐based thresholds are applied but also the steroid profile is monitored via the Athlete Biological Passport whereby the individual reference ranges derived from multiple test results of the same athlete are compared to population‐based thresholds. In order to maintain a high probative force of the passport, samples collected or analyzed under suboptimal conditions should not be included in the longitudinal review. This applies to biologically affected or degraded samples and to samples excluded owing to the presence of other substances potentially (or evidently) altering the steroid profile. Nineteen different doping agents comprising anabolic steroids, selective androgen receptor modulators, selective estrogen receptor modulators, ibutamoren, and tibolone were investigated for their effect on the steroid profile using an androgen receptor activation test, an androgen receptor binding assay, an aromatase assay, and a steroidogenesis assay. The in vitro tests were coupled with well‐established liquid chromatography/mass spectrometry‐based analytical approaches and for a subset of steroidal analytes by gas chromatography/mass spectrometry. The variety of tests employed should produce a comprehensive data set to better understand how a compound under investigation may impact the steroid profile. Although our data set may allow an estimate of whether or not a substance will have an impact on the overall steroid metabolism, predicting which parameter in particular may be influenced remains difficult. Abstract : Nineteen different doping agents were investigated regarding their potential to alter the steroid profile employing an androgen receptor activation test, an androgen receptor binding assay, an aromatase assay, and a steroidogenesis assay. The results obtained suggest the possibility to estimate whether or not a substance will have an impact on the overall steroid metabolism, but predicting which parameter in particular may be influenced remains difficult. The results obtained on tibolone employing the steroidogenesis assay are exemplarily depicted.